Strategi Penguatan Ekonomi Ummat Melalui Kantin Sehat pada Komunitas Warga Sekitar Darul Ihsan MBS Sragen - Eko Wijiyono; Mahfud Effendi; Tobroni Tobroni; Joko Widodo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This study aims to analyze the strategy of community economic empowerment through the management of a Healthy Canteen at the Darul Ihsan Muhammadiyah Islamic Boarding School (Pondok Pesantren) in Sragen. The study uses a qualitative approach with the Participatory Action Research (PAR) method, involving the community as active subjects in the entire research cycle. The mentoring shows that the community has economic potential in the form of local raw materials and cooking skills that have not been optimally utilized. The Collaborative Trilogy Model of Boarding School-Community-Students was developed by integrating the Asset-Based Community Development (ABCD) approach with the principles of a circular economy. This model successfully created a local value chain: farmers as suppliers, housewives as processors, and students as the main consumers. The management of the Healthy Canteen is an effective and sustainable empowerment strategy. This model can be applied to other Islamic boarding schools with contextual adjustments, serving as a blueprint for economic empowerment based on religious institutions that integrates Islamic values, local wisdom, and social business principles.